If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -13X + 20 = -11X Reorder the terms: 20 + -13X = -11X Solving 20 + -13X = -11X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '11X' to each side of the equation. 20 + -13X + 11X = -11X + 11X Combine like terms: -13X + 11X = -2X 20 + -2X = -11X + 11X Combine like terms: -11X + 11X = 0 20 + -2X = 0 Add '-20' to each side of the equation. 20 + -20 + -2X = 0 + -20 Combine like terms: 20 + -20 = 0 0 + -2X = 0 + -20 -2X = 0 + -20 Combine like terms: 0 + -20 = -20 -2X = -20 Divide each side by '-2'. X = 10 Simplifying X = 10
| V=1385n+18790 | | A^2=2209 | | 5x+4g=c | | 8=-3x+2(x-4) | | 6-2x=22 | | 4g+7=4g-1 | | 4(2x+1)-3(y+1)= | | -2=-1.75+k | | 12r^2-75=0 | | -2=7+k/(-4) | | 4(w+3)=w- 15 | | X=3x+12 | | 40+400+1= | | 7(3-y)=-3x+4 | | 21x+6=17x-16 | | -d^2+18d-81=0 | | -13X+20=-11 | | (5x-20)=3x | | 7h-3h-6=6 | | 5(x-1)(x+4)(2x-3)=0 | | -2=-1.75k | | 25=5(9x-4) | | 2x-9=6x-13 | | -2(3)+5+5(3)= | | 6x-2=12x+1 | | 2x^3-3x-20=0 | | y-(-16)=-12 | | -18+30=-4(x+5) | | x+(-24)=-38 | | -4(x+3)=4 | | 1x/19=20 | | .42*n=.6 |